Achieving sustainable universal primary education through debt relief: The case of Kenya - Nancy N. Nafula (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This study critically reviews the education sector in Kenya and the challenges facing the sector in achieving universal primary schooling. The study argues that the introduction of cost-sharing system in Kenya has resulted in high dropout and repetition rates, low transition and completion rates. These problems are exacerbated by the fact that children from poor households, whose parents cannot afford to pay fees, end up dropping out of school. Lack of textbooks has also resulted in poor performance in the national examination. The study also notes that as much as the government is subsidizing education in terms of paying teachers, reduction of debt overhang is important and that debt servicing must be addressed to free resources for social service provision, the case of education. The study argues that much more fiscal resources are being spent on servicing both external and domestic debts than are being spent on education and health. The paper therefore justifies the case for universal primary schooling in Kenya through debt relief. It discusses the key priority areas in education where resources from debt relief could be spent effectively to achieve sustainable universal primary education.
Keywords: I12; I13; 330; debt relief; primary schooling; universal education; Allgemeinbildende Schule; Öffentliche Bildungsausgaben; Schuldenerlass; Kenia